INFLUENCE OF DRIP IRRIGATION ON GROWTH, NUT CHARACTERS AND YIELD OF COCONUT IN LITTORAL SANDY SOIL - R. Dhanapal; H.P. Maheswarappa; P. Subramanian (International Coconut Community Journal, 2002)
A field experiment was conducted at Central Plantation Crops Research Institute, Kasaragod, India for six years (1993-1999) to study the impact of drip irrigation levels and mulching on coconut in littoral sandy soil. The treatments consisted of three levels of drip irrigation (66, 100, and 133 % of open pan evaporation (E0)) along with basin irrigation (100 % of E0) and rainfed control as main plot treatments and mulching with coconut leaves and no mulching as sub plot treatments. The experimental results revealed that annual leaf production and leaf nutrient status of coconut was better in the irrigated treatments compared to the rainfed control. The drip irrigation at 66 per cent of E0 (27 litres of water per palm per day during December-January months and 32 litres of water per palm per day during February-May months) resulted in water saving and the nut yield was on par with 100 per cent and 133 per cent of E0 through drip and 100 per cent of E0 through basin irrigation and differed significantly compared to rainfed control. The nut characters like nut weight, husk weight, copra thickness, copra content and copra yield was superior under irrigated treatments compared to rainfed control. The copra yield was 499 kg per ha under rainfed condition, where as it was 2087 to 2202 kg per ha under irrigated treatments. Irrigation along with mulching with coconut leaves resulted in significantly higher nut yields.